Massive/Micro Sensemaking: Towards Post-Pandemic Futures - Luka, Mary Elizabeth; Markham, Annette N; Harris, Dan (Imaginations)

(untitled) (York University, 2021)
In what ways have forms for engendering the interconnection and materiality required for creative production changed in the time of COVID-19? How and why have our notions of imagining and visualizing cross-cultural production and its modes of research, analysis, and representation shifted? The global pandemic and responses to it through various forms of cultural production have seen an explosion of productivity and collective social actions as well as the reinforcement of entrenched systemic racism and other forms of discrimination and imbalance. In this special issue, authors weave together a series of dialogues, methodological approaches, and materialities that reflect on the visuality of the experiences that were first developed through shared critical autoethnographic practices during and after an international Massive Micro Sensemaking experiment involving 165 people.